2006
DOI: 10.1111/j.1464-410x.2006.06202.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the number of renal glomeruli in reflux nephropathy

Abstract: determined to explore the potential association between these variables and the total renal scars, renal function (glomerular filtration rate, GFR), or daily urinary protein excretion. RESULTSThe number of glomeruli was closely correlated with the actual size of glomeruli ( y = 14.783 − 0.052 x, R = 0.782). To a lesser extent, the number of glomeruli was also closely correlated with the size of glomeruli expressed in SD s ( y = 6.264 − 0.832 x, R = 0.630). There was a good correlation between the number of glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…[10,16] However, from the results of this study, we confirmed that the renal functional reserve was still present in patients with a glomerular size of < +4SD, and the positive effects of therapeutic intervention were thus expected in these patients.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…[10,16] However, from the results of this study, we confirmed that the renal functional reserve was still present in patients with a glomerular size of < +4SD, and the positive effects of therapeutic intervention were thus expected in these patients.…”
Section: Discussionsupporting
confidence: 69%
“…[10,16] For the treatment of RN, early intervention is therefore necessary to minimize the decrease in nephrons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…decreased glomerular filtration rate), proteinuria and/or hypertension, indicate progressive RN. It is generally thought that RN progresses when the remnant normal region mass, a decrease of which negatively correlates with an increase in the damaged region mass in the renal parenchyma, is reduced to the level below threshold, but details, such as marginal regions, remain unknown . Many patients with progressive RN have bilateral multiple renal parenchymal injury …”
Section: Pathology Of Rnmentioning
confidence: 99%
“…Reflux nephropathy is the main concerning as 13~25% of patients develop end-stage renal disease from the inflammatory and immunological processes (Askari and Belman 1982;Craig, Irwig et al 2000;Ardissino, Avolio et al 2004). The risk of developing "Reflux nephropathy" is multiprediposing and related to the host susceptibility and virulence of bacteria (Matsuoka, Nakashima et al 2006;Cendron 2008;Coulthard 2008). Although the management of VUR remains controversial, the ultimate goal is to prevent the further renal injury from reflux and repeat UTIs.…”
Section: Vur and Associated Abnormalitiesmentioning
confidence: 99%